PERLINDUNGAN HUKUM DALAM PERJANJIAN KERJA LAUT BAGI PELAUT BERDASARKAN MARINE LABOUR CONVENTION - Moch Zainuddin (Jurnal Hukum dan Etika Kesehatan, 2021)
Seafaring is a profession that is full of challenges, the need for the profession of seafarers in the world is increasing in direct proportion to the rate of increase in the world economy. Indonesia is one of the members of the IMO (International Maritime Organization), with a number of seafarers of more than one million workers, which are expected to become a commodity for seafarers to be able to increase foreign exchange earnings for the State of Indonesia as a member of the IMO who attended the 2006 MLC conference which was held in Geneva, Switzerland. . With the presence of Indonesia as a member of the IMO at the 2006 MLC, the State is present in legal protection for the welfare of seafarers in Indonesia which is equivalent to the welfare of world seafarers regarding the arrangement of work contracts and seafarers' salaries, there are still salaries that are below the standard not in accordance with the rules of the ILO (International Labor Organization). ) a minimum of $ 614 or Rp. 8,643,769,- (exchange rate of $1 = Rp. 14,077,-). The government is still implementing regulations regarding the wages of Indonesian seafarers in accordance with the UMR of the area where the domicile of the shipping company is located. This discrepancy creates a conflict of legal norms. Legal protection for seafarers, especially regarding welfare, needs to be applied referring to Government Regulations and Legislation and supervised by a body formed by the government for the sake of the principle of justice in the world of work for the seafaring profession.